(untitled) (Damascus University Journal of agriculture sciences, 2024)
This recherche was performed to determine the physic-chemical properties of oil extracted from non-irradiated thyme meal and irradiated samples irradiated with 15 kGy of gamma irradiation. The results indicated that the irradiation did not cause any significant change in acid value (AV), peroxide value (PV), Thiobarbituric acid (TBA), iodine value (IV), saponification value (SV), and refractive index (RI). The result obtained shows that the investigated indicators are within the stipulated limits recommended by local and international standards. The results showed that the thyme meal oil had high concentration of unsaturated fatty acids (84.38%), and low concentration of saturated fatty acids (15.71%). The unsaturated and saturated fatty acids ratio of thyme meal oil is (USFA/SFA=5.45). The saturated fatty acids of thyme meal oil increased significantly (P<0.05) in irradiation samples. While, the irradiation decreased the unsaturated fatty acids in thyme meal oil. The results of demonstrated the beneficial use of irradiated processing in improving the safety and extending the shelf life of thyme meal.